2009
DOI: 10.1103/physrevb.80.115216
|View full text |Cite
|
Sign up to set email alerts
|

Classical spins in topological insulators

Abstract: Following the recent theoretical proposal and experiment on quantum spin Hall effect in HgTe/CdTe quantum wells, we consider a single magnetic impurity localized in the bulk of the system, which we treat as a classical spin. It is shown that there are always localized excited states in the bulk energy gap for arbitrarily strong impurity strength in inverted region, while the localized excited states vanish for very strong impurity strength in normal region. Similar conclusion also applies to three-dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 23 publications
5
73
0
Order By: Relevance
“…σc(ω) in the far-infrared region becomes clearly depressed with decreasing temperature and the suppressed spectral weight seems not to be recovered by 5000 cm 45 (as well as in the underdoped cuprates) is transferred to higher energies and not to the region below the low-frequency cutoff of our data. The latter effect would have resulted in drastic increases of R c (ω) and the c axis dc conductivity, which is not supported either by our own reflectance or resistivity data (of FeTe 0.6 Se 0.4 compound [26]). The oscillator strength sum rule implies a conservation of the global spectral weight.…”
mentioning
confidence: 63%
“…σc(ω) in the far-infrared region becomes clearly depressed with decreasing temperature and the suppressed spectral weight seems not to be recovered by 5000 cm 45 (as well as in the underdoped cuprates) is transferred to higher energies and not to the region below the low-frequency cutoff of our data. The latter effect would have resulted in drastic increases of R c (ω) and the c axis dc conductivity, which is not supported either by our own reflectance or resistivity data (of FeTe 0.6 Se 0.4 compound [26]). The oscillator strength sum rule implies a conservation of the global spectral weight.…”
mentioning
confidence: 63%
“…The effects of the effective Hamiltonian on the decoherence has been studied in many papers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Especially, dramatic manifestation of the decoherence has often been found in the vicinity of the quantum critical point of the effective Hamiltonian.…”
mentioning
confidence: 99%
“…The bound state, on the other hand, is induced when the system is topologically nontrivial. Even a potential scattering 18 or a vacancy 19 could produce the in-gap bound state in the bulk of TIs. Therefore, the in-gap bound state could be considered as a degree of freedom, while its energy is determined by the impurity.…”
Section: Self-screening Of the Kondo Effectmentioning
confidence: 99%
“…[23][24][25][26][27] For these reasons, it is important to study how the quasiparticle states are affected when vacancies or impurities are localized in the bulk of the system. It has been shown that classical spins 18 or vacancies 19,20 localized in the bulk of TIs could result in the coexistence of in-gap bound states and boundary states. For a quantum impurity, the quantum fluctuations of its internal degree of freedom play an important role, making it significantly differ from classical impurities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation